The Impact of Self-Esteem and Media Literacy on Personal Branding Strategies on Instagram Among Generation Z - Audrew, Edelweis; Herdiansyah, Haris (ETTISAL : Journal of Communication, 2024)
In today's digital era, social media platforms such as Instagram play a key role in self-expression. This research investigates the dynamic interplay between self-esteem, media literacy, and personal branding strategies on Instagram within Generation Z, considering self-perception as a pivotal intervening variable. The study aims to understand the nuanced relationships and their impact on the digital identities crafted by individuals in this demographic. Employing a quantitative research approach, the study utilizes Path Analysis to analyze the complex relationships among self-esteem, media literacy, personal branding strategies, and self-perception. The primary data collection method involves online surveys through structured questionnaires distributed to a diverse sample of Generation Z Instagram users. Preliminary findings reveal significant correlations between self-esteem, media literacy levels, and the adoption of distinct personal branding strategies on Instagram within Generation Z. The research also identifies self-perception as a crucial intervening factor that influences the nature and effectiveness of personal branding efforts on this social media platform. The study enhances insights into factors influencing personal branding on Instagram for Generation Z. Recognizing the roles of self-esteem, media literacy, and self-perception, it offers valuable insights for educators, marketers, and social media users navigating online self-representation complexities.